Focal glial detection coincides with precedes amyloid plague formation in APPPS1 transgenic mice by PCR - Abbas, Talib (Iraqi Journal of Science, 2023)
The identification and sequencing of Amyloid Precursor Protien (APP) and presenilin (PS) opened the door for the engineering of transgenic mouse models to study pathogenic mechanisms of Alzheimer Disease (AD). The first successful mouse models over-expressed human APP with an Familiar AD (FAD) linked mutation in the brain. These mice exhibit Aß plaques, neuron loss, dystrophic neurites, inflammatory responses, learning impairments and deficits in synaptic transmission and/or long-term potentiation. The genotypes of all offspring of APP/PS1 mutant mice are analysed by Polymerise Chain Reactions. Generally there are two possibilities to analyse the DNA. The First, primers for APP or PS1 was used separately assuming that both genes are integrated into the transgene. The second possibility is to do both amplifications in one PCR. Transgene mapping revealed that both transgenes were integrated at the lower arm of chromosome 2 between 40 and 60 cM. The result showed a clear band of APP gene. By using many gel concentrations( 1%, 2%, 5%). The 2% gel concentration is the best to visualize the band in 150 V at 1 hour, in order to optimize the method. The Polymerise Chain reaction method (PCR) also had been optimized, in order to have a band of APP. Considering the number of studies that rely on the detection of AD pathology, it is surprising to find such high variability in the APPPS1gene PCR of key AD-related markers across pretreatments in adjacent Aβ Accumulations of gene manipulation.